P060 Reproductive and Sexual Function in Men With IBD in Brazil. (December 2019) - Machado, Marta; Lima, Fernanda
Abstract : BACKGROUND: There are studies focusing on fertility, pregnancy and sexual issues for women with inflammatory bowel disease. On the other hand, relatively little attention has been focused on reproductive and mainly sexual function issues faced by men with IBD. Sexual function may be adversely affected by some medications used to treat IBD, the depression that may accompany active IBD, and proctocolectomy. The present study aims to evaluate the reproductive and sexual function of patients with IBD in Brazil. METHODS: This prospective study was conducted by a self-completed cross-sectional online questionnaire answered by 225 male IBD patients over 18 years of age throughout Brazil in 2019 for 10 weeks. RESULTS: A total of 225 patients answered the questionnaire, 78.2% were between 18 and 38 years old, 69.67% were diagnosed with Crohn's disease, 27.96% ulcerative colitis and 2.37% indeterminate colitis. 50.24% had children, 42.48% were using contraception, 33.02% did not plan pregnancy, 28.78% of patients reported that the disease disrupted family planning, 70.37% did not consider having more children., were taking the following medications when their wives became pregnant 20, 31 5-ASA, 12.5% Corticosteroids, 11, 71 Immunosuppressants, 14.84% Biological, 0.003% Antibiotic, 47.65% without any treatment. Of the patients studied, 30.14% have an erection problem, 20.45% sought the help of a urologist, 32.55% of the patients underwent surgery for the treatment of IBD, 87.56% reported that their doctors never addressed the issue. family planning during treatment and 13.81 of the patients proactively approached the issue with their doctors. CONCLUSION(S): The data presented show that family planning is little explored by both doctors and male patients. Inflammatory bowel diseases may influence family planning with regard to not having children or considering having more children. Sexual dysfunction can occur in a considerable number of patients, but few seek expert help.